PENGARUH KESELAMATAN KESEHATAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT HARAPAN JAYA SENTOSA - Saputra, Irvan Maulana; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2020)
ABSTRACT The problem in PT Harapan Jaya Sentosa is quite high, the reason there are still many employees who do not obey the rules of safety such as not using personal protective equipment, wear occupational health safety equipment is not appropriate, not obedient to the work procedures, and do the work that does not comply with its employees. The purpose of this research is to determine the influence of occupational health safety and work discipline on the employee's performance at PT Harapan Jaya Sentosa. This research uses quantitative methods. and use simple random sampling technique. The formula used to determine the sample count is to use the Slovin formula with an error rate of 5%. The study used multiple linear regression analysis methods, with a sample count of 102 respondents. The measurement and scale measurement methods in this study use the Likert scale. Data collection using questionnaires, with the help of SPSS version 26 program. The results of the study showed that partial occupational health safety has a significant impact on employee performance, indicated by T Count of 6.917 > T table 1.984 sig. 0.000 < 0.05. Then the work discipline is significant to the performance of employees with the T count of 10.611 > T table 1.984 with the level of sig. 0.000 < 0.05. Then occupational health safety and work discipline significantly affect employees ' performance simultaneously demonstrated by the value of F count 121,628 > 3.08 with significance rate of 0.000 < 0.05. Keywords: occupational health safety; work discipline; employee performance.